Sistem Parkir Pintar (Menuju Smart Campus dengan Internet of Things) - Ridho Rinaldi Erpa; Wiwik Wiharti -; Ihsan Lumasa Rimra (Pusat Penelitian dan pengabdian kepada Masyarakat (P3M) Politeknik Negeri Padang, 2018)
Smart Parking (SP) is one of many technologies to be implemented in order to enhance the infrastructure of Information and Communication Technology (ICT). All objects and devices at the parking lot will become entities. They are integrated and embedded into electronic devices that will form the Internet of Things (IoT). Smart Parking (SP) will be able to make parking arrangements and management in real time. The academic community will be able to find an empty parking space (slot) because of the parking location with intelligent systems, cameras and sensor devices in front of the gate or in the parking lot. Using this technology, the academic community may request the services as well as automatically informed will be notified of an empty slot.